A concordance between industries and technologies: matching the technological fields of the Patentatlas to the German industry classification - Tom Broekel (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
The Patentatlas by Greif and Schmiedl (2002) represents an important source for patent data in Germany. Its use for industry-specific studies is however problematic because the correct assignment of patent data classified by technological fields to commonly used industry classifications is unclear. This paper presents an application-oriented approach to this issue. In using industryspecific R&D employment numbers on a regional level, an approximate concordance is developed between the 31 technological fields of the Patentatlas and 21 manufacturing industries, as defined by the German Industry Classification.
Keywords: O18; O34; R12; 330; Patentatlas; Industry Classification; IPC; NACE; Concordance; Patent; Technologie; Statistik; Verarbeitendes Gewerbe; Klassifikation; Deutschland